Strategi Guru Fiqih Menanamkan Nilai Panca Cinta melalui Kurikulum Berbasis Cinta di MIN Kota Bukittinggi - Tiara Ayu Wahyuni; Alimir Alimir (ARZUSIN, 2026)
Although strategies used by Fiqh teachers to instill the values of Panca Cinta through the Kurikulum Berbasis Cinta (KBC) have received attention in various studies, research that specifically discusses the integration of these values into Fiqh learning at the madrasah ibtidaiyah level remains limited. This study aims to explore the strategies of Fiqh teachers in instilling the value of Panca Cinta through KBC and to identify its supporting and inhibiting factors. This study used a qualitative approach with a field study design, involving informants consisting of Fiqh teachers, fourth-grade students, and the principal selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed using interactive data analysis techniques comprising data reduction, data display, and conclusion drawing. The results showed that Fiqh teachers applied strategies of habituation, exemplification, giving advice, and integrating values into learning materials. The value of Panca Cinta was reflected in students’ behavior, such as increased discipline, responsibility, environmental awareness, and mutual respect. Supporting factors included a religious school environment and institutional support, whereas inhibiting factors included limited time, differences in students’ characteristics, and the influence of the external environment. These findings contribute to the development of Islamic education, particularly in the integration of cognitive, affective, and psychomotor aspects in value-based learning, while also expanding understanding of character education within the KBC framework. This study concludes that teacher consistency and contextual learning strategies play an important role in students’ character formation and emphasizes the need to strengthen value-based learning practices in madrasah ibtidaiyah.